Barmhärtiga svenskar och tacksamma flyktingar: Ett beredskapssjukhus sommaren 1945 i svensk press - Roos, Lena (Nordisk judaistik, 2008)
In June of 1945 Sweden agreed to receive 10 000 former prisoners of German concentration camps for medical care. Approximately 1 200 of these were to be assigned to a temporary hospital in the small Swedish town of Sigtuna. A study of how a selection of Swedish daily papers describe this event shows that the reporters tend to focus more on the Swedish hospital staff than on the refugees. The refugees are merely portrayed as the recipients of Sweden’s humanitarian assistance. In these articles, the refugees have no past and no future. Their role is merely to express their gratitude and to recover, thereby testifying to the efficacy of the Swedish hospital. Life in the hospital in Sigtuna is described as close to paradise. That many of the patients were in such poor condition so that they died shortly after their arrival in Sigtuna is rarely mentioned. These tendencies in the articles about the Sigtuna hospital can be connected to Sweden’s postwar need to redeem its tarnished reputation as a neutral country by portraying itself in public debate as the champion of a humanitarian tradition. It can also be analysed on the basis of what other studies have shown of how Swedish reporters of the 1980s and 1990s constructed an idealistic picture of Sweden and the Swedes by describing immigrants and refugees as the essential Other.